Dimensi Soft Skill Generasi Z di Dunia Hospitaliti: Membangun Keunggulan Kompetitif dengan Critical Thinking, Creativity, dan Problem Solving - Indrayani, I Gusti Ayu Putu Wita; Yadnya, I Gede Parta; Pramana, I Wayan Arya Yudha Galang; Putra, Putu Eka Purnama; Putra, I Nyoman Pebriandika Sukawati (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
Generation Z faces dynamic and increasingly complex demands in the job market. Thisresearch aims to identify critical soft skill dimensions for Generation Z employees in thehospitality industry. Employing a qualitative approach, the study explores this phenomenonthrough semi-structured in-depth interviews with ten Department Heads of star-rated hotelsin Badung and Denpasar. The research also unveils perspectives and experiences of star-ratedhotel managers in guiding Generation Z employees and addressing associated challenges.Findings indicate the necessity of developing key soft skills, including critical thinking,creativity, and problem-solving. Critical thinking enables them to analyze informationcritically and make prompt decisions, while creativity supports innovative behavior and freshperspectives on issues. Additionally, problem-solving becomes an essential skill in facingcomplex challenges and changes. The study's implications emphasize the importance ofintegrating these three soft skills to prepare Generation Z for challenges in the hospitalitysector. The research underscores the need for integrating these skills to form a robustfoundation for Generation Z's future in the ever-changing and dynamic hospitality industry.